Quantifying the effect of labor market size on learning externalities - Jan Cornelius Peters (Kiel University, Department of Economics, 2016)
This paper provides empirical evidence that individual labor productivity significantly depends on the size of the local labor market in which a worker previously acquired work experience. The analysis uses German micro data from the Institute for Employment Research (IAB) on transitions to employment within the period 2005 to 2011 and individual employment biographies from 1975 onwards. Analyzing the wages associated with the newly established employment relationships, suggests that dynamic agglomeration economies in general, and learning externalities in particular, play an important role in explaining individual labor productivity. Workers receive a significantly higher wage after acquiring experience in urban than in non-urban labor markets. Doubling local employment in all labor markets where experience was acquired, increases the productivity of a worker with two years of work experience by more than 0.7 percent. After 10 years of experience the corresponding gain amounts to about three percent, after 30 years to about four to five percent. A key factor seems to be an above average share of high-skilled labor within large urban labor markets which is supposed to enhance local learning opportunities.
Keywords: R10; R23; J31; 330; Agglomeration economies; Human capital externalities; Learning; Urban wage growth premium; Transition to employment